The Contribution of Education, Health, and Unemployment on HDI in East Java, Indonesia - Rosyid, Amrun; Damayanti, Elok; Sarmilah, Sarmilah; Rohani, ST; Shabila, Syalwa (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: This study aims to analyse the influence of education, health, and unemployment on the Human Development Index (HDI) in East Java, Indonesia. Given the disparities in HDI across regions, this research seeks to identify the extent to which these factors contribute to HDI variations in the province. Design/methodology/approach: A quantitative research approach was employed, using secondary data from the Central Bureau of Statistics (BPS) of East Java for the years 2021 and 2022. The study analysed data from 38 regencies/cities in East Java, using multiple linear regression to examine the impact of education (average years of schooling), health (number of hospitals), and unemployment (percentage of the labour force) on HDI. Findings: The results indicate that education and health have a significant positive impact on HDI, while unemployment has a significant negative effect. The findings confirm that increasing education levels and improving healthcare access contribute positively to human development, whereas higher unemployment rates hinder HDI growth. The coefficient of determination (R²) suggests that these three factors collectively explain a substantial portion of HDI variation in East Java. Research limitations/implications: This study is limited to secondary data analysis and does not consider qualitative factors such as policy effectiveness, governance, and social infrastructure that may also influence HDI. Future research should incorporate qualitative methods and longitudinal data to capture broader determinants of human development. Practical implications: The findings provide valuable insights for policymakers in East Java to focus on education and healthcare improvements while addressing unemployment challenges. Policy recommendations include expanding access to quality education, improving healthcare facilities in underdeveloped areas, and implementing effective employment programs to reduce regional disparities in HDI. Originality/value: This research contributes to the understanding of HDI determinants at the provincial level in Indonesia, offering empirical evidence on the interplay between education, health, and unemployment. The study highlights the need for integrated policy approaches to enhance human development in East Java. Paper type: Research paper